0067 Humanized Chemogenetic Approach to Treat Sleep Apnea. (12th April 2019) - Curado, Thomaz A Fleury; Pho, Huy; Freire, Carla; Sennes, Luiz U; Fuller, David; Michaelides, Mike; Schwartz, Alan R; Polotsky, Vsevolod Y
Abstract: Introduction: Obstructive Sleep Apnea (OSA) is a prevalent condition and a major cause of morbidity and mortality. OSA contributes to the development and progression of neurocognitive, metabolic, cardiovascular, and oncologic diseases. The tongue and specifically genioglossus (GG) muscle have been implicated in the pathogenesis of upper airway (UA) obstruction during sleep. Nasal positive airway pressure can treat OSA but poor adherence severely limits its effectiveness. We have previously shown that obese C57BL/6J mice have OSA, similar to humans. We have also shown that DREADDs deployed by intracerebral injection in the XII nucleus and activated with specific ligand clozapine-N-oxide (CNO) increases UA patency in mice. Several challenges preclude the translational use of our previous approach including (a) intracerebral injections; (b) CNO conversion psychotropic active clozapine. We hypothesized that, in mice, UA patency can be improved and sleep apnea can be treated by injecting DREADD carried by an adeno-associated virus type 9 (AAV9) capable of retrograde neuronal transport and activated by a novel ligand JHU37160 (J60). Methods: Excitatory DREADD (AAV9-hSyn-hM3(Gq)-mCherry n=10) or Control AAV9-hSyn-GFP (n=5) was delivered bilaterally by tongue injection to mice with diet induced obesity. Six weeks after the delivery, mice were injected with J60 or saline intraperitoneally (IP) using a cross-over design and submitted to GG electromyography (EMGGG), UA dynamic MRI and sleep studies. Results: In all mice 15 mice DREADDs or control virus were expressed in the hypoglossal nucleus confirming effective retrograde transport after the GG injection. DREADDs transfected mice showed a striking 7.05 fold increase in tonic EMGGG activity and nearly 2 fold increase in EMGGG activity after J60 injection (p<0.001). In MR imaging, axial dynamic images demonstrated significant pharyngeal dilation At the rim of the soft palate upon the ligand administration (0.46 ±0.03mm 2 to 1.16±0.05mm 2, p<0.05). Sleep studies currently in progress. Conclusion: Lingual muscles can be successfully stimulated using retrograde transgenic approach to activate motor neuron groups in selected brain areas. Our results suggest that retrograde delivery of DREADD to the hypoglossal nucleus effectively controls pharyngeal patency and may treat OSA Support (If Any): R01HL138932-0 and ATS Unrestricted Grant.